ABO rs657152 and Blood Groups Are as Predictor Factors of COVID-19 Mortality in the Iranian Population. (14th November 2022) - Mirzaei Gheinari, Fahimeh; Sakhaee, Fatemeh; Gholami, Melika; Sotoodehnejadnematalahi, Fattah; Zamani, Mohammad Saber; Ahmadi, Iraj; Anvari, Enayat; Fateh, Abolfazl
Abstract : Several studies have discovered a relationship between specific blood types, genetic variations of the ABO gene, and coronavirus disease 2019 (COVID-19). Therefore, the aim of this study was to evaluate the association between ABO rs657152 polymorphisms and ABO blood groups with COVID-19 mortality. The tetraprimer amplification refractory mutation system, polymerase chain reaction method, was used for ABO rs657152 polymorphism genotyping in 1, 211 dead and 1, 442 improved patients. In the current study, the frequency of ABO rs657152 AA than CC genotypes was significantly higher in dead patients than in improved patients. Our findings indicated that blood type A was associated with the highest risk of COVID-19 mortality compared to other blood groups, and patients with blood type O have a lower risk of infection, suggesting that blood type O may be a protective factor against COVID-19 mortality. Multivariate logistic regression test indicated that higher COVID-19 mortality rates were linked with alkaline phosphatase, alanine aminotransferase, high density lipoprotein, low-density lipoprotein, fasting blood glucose, uric acid, creatinine, erythrocyte sedimentation rate, C-reactive protein, 25-hydroxyvitamin D, real-time PCR Ct values, ABO blood groups, and ABO rs657152 AA genotype. In conclusion, the AA genotype of ABO rs657152 and blood type A were associated with a considerably increased frequency of COVID-19 mortality. Further research is necessary to validate the obtained results.